2014
DOI: 10.1177/1479164114524584
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of peripheral vascular disease and its association with carotid intima-media thickness and arterial stiffness in type 2 diabetes: The Chennai Urban Rural Epidemiology Study (CURES 111)

Abstract: We investigated the prevalence of peripheral vascular disease (PVD) and its association with preclinical atherosclerotic markers [intima-media thickness (IMT)] and arterial stiffness among 1755 urban south Indian type 2 diabetic subjects recruited from the Chennai Urban Rural Epidemiology Study (CURES). Doppler studies were performed, and PVD was defined as ankle-brachial index (ABI) of ≤0.9. IMT of the common carotid artery was determined using high-resolution B-mode ultrasonography, and augmentation index (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 52 publications
2
20
2
Order By: Relevance
“…28 In a prospective cohort of 145 PAD patients, Pradeepa et al found an association between augmentation index and PAD, but this association was lost when adjusting for age. 29 Finally, Beckmann et al demonstrated a higher central AIX in abdominal aortic aneurysm and PAD patients compared to healthy controls, but their control group was significantly younger and healthier than controls in the present study, which also included patients with aneurysmal disease. 17 Overall, the present study adds to the literature by demonstrating in one of the largest samples an independent association between AIX and PAD.…”
Section: Discussioncontrasting
confidence: 56%
“…28 In a prospective cohort of 145 PAD patients, Pradeepa et al found an association between augmentation index and PAD, but this association was lost when adjusting for age. 29 Finally, Beckmann et al demonstrated a higher central AIX in abdominal aortic aneurysm and PAD patients compared to healthy controls, but their control group was significantly younger and healthier than controls in the present study, which also included patients with aneurysmal disease. 17 Overall, the present study adds to the literature by demonstrating in one of the largest samples an independent association between AIX and PAD.…”
Section: Discussioncontrasting
confidence: 56%
“…Although there are inconsistencies among studies regarding the risk factors, PAD is a major risk factor for LEA, in agreement with our results ( P = 0·001, OR = 9·07). PAD is commonly seen in individuals with type 2 diabetes, in whom it occurs almost threefold more frequently compared with age‐ and sex‐matched non‐diabetic individuals .…”
Section: Discussionmentioning
confidence: 99%
“…Available data also suggest that the susceptibility of Asian Indians to the complications of diabetes mellitus differs from that of the Western population [36][37][38][39] . The vascular complications of T2DM account for the majority of the social and economic burden.…”
Section: Burden Of Diabetesmentioning
confidence: 99%